Differentiations in Visibility-Male Advantages and Female Disadvantages in Gender-Segregated Programmes - Heikkilä, Mia; Isaksson, Anna; Stranne, Frida (Frontiers in Sociology, 2020)
This article stresses the importance of understanding that women and men in gender-segregated programmes experience their minority positions very differently. It stems from an interest in the kind of interventions that academia should address in order to reduce gender segregation and provide women and men with the same educational opportunities and personal development. In relation to the obvious and continuing gender differences along a horizontal dimension, previous research seems to have had a limited impact in breaking gender stereotypes and promoting women and men to more atypical fields. The empirical data consists of 24 semi-structured, individual interviews from underrepresented students’ gender-related experiences/thoughts about their programmes. By using the concepts of ‘visibility,’ ‘sense of belonging’ and ‘negotiating otherness’ to analyze how negotiation and belonging are part of students’ everyday university lives this study’s most important contributions are its findings regarding the differentiations in visibility. A continuum of visibility experiences is explored, from men who receive positive attention to women who are unaware of the negative assumptions being made about them. Our visibility scale indicates, as does previous research, that there are differences between female and male minorities but also within both groups of students. This knowledge is crucial when designing interventions so as to provide positive study environments for both women and men. Also – in a broader perspective – it is important in order to recruit and ensure that minority gender students remain in the programs.